Unraveling the head-fake effect: Dynamic measures of cognitive conflict in sport contexts - Güldenpenning, Iris; Schulze Freilinghaus, Lars; Böer, Nils Tobias; Weigelt, Matthias (57. Herbsttagung experimentelle Kognitionspsychologie (HexKop))

How does practice modulate fake-production costs in a basketball task? Analyses of frequency distributions and mixture effects - Böer, Nils Tobias; Schütz, Christoph; Weigelt, Matthias; Güldenpenning, Iris (Psychological Research)
Abstract The execution of incompatible actions imposes costs on action planning, commonly known as response-response incompatibility-costs. This phenomenon is also evident in sports: A basketball player who performs a pass in one direction whilst orienting the head into the contrary direction (pass with head fake) needs more time to initiate the action as if pass direction and head orientation are the same (pass without head fake). The aim of this study was twofold: First, we present a re-analysis of the data from Böer et al. (Psychological Research 88:523–524, 2024) using mixture effect modelling (Miller, Behavior Research Methods 38:92–106, 2006) explore if fake-production costs manifest continuously (uniform effect) in all participants or if some participants show fake-production costs occasionally but substantially (mixed effect). Second, we collected data of a control group which was analysed with the previous data of the practice group and fitted initiation times (ITs) to an ex-Gaussian distribution. The analysis of mixture effects revealed that most participants exhibited a uniform effect when they didn’t have time to mentally prepare the movement. This pattern was not changed by practice, suggesting fake-production costs can’t be overcome by practice alone without mental preparation time. The analysis of mean ITs revealed improvements in the practice group but not in the control group, independent of the type of pass performed. The distribution analyses complemented these findings as it showed that the improvement in participants’ performance with increasing practice can mainly be attributed to a reduction of the exponential part of the distribution (parameter tau).
Keywords: Sport Psychology; Sport Science; Deception; Distribution Analysis

The mere presence of a social partner modulates fake-production costs - Böer, Nils Tobias; Güldenpenning, Iris; Weigelt, Matthias (57th Herbsttreffen der experimentellen Kognitionspsychologie (HExKoP))
Keywords: Deception; Sport Psychology; Social Interaction

Trendbericht: Organische Chemie 2025 - Breugst, Martin; Andexer, Jennifer; Barra, Lena; Beil, Sebastian B.; Bierbach, Sascha; Burkhardt, Immo; Dumele, Oliver; Ernst, Martin; Frommer, Jennifer; Gellrich, Urs; Germer, Philipp; Giese, Michael; et al. (Nachrichten aus der Chemie)
Abstract Highlights von November 2023 bis 2024: die erste Einelektron‐C–C‐σ‐Bindung und Anti‐Bredt‐Verbindung; gesättigte Heterocyclen elektrochemisch funktionalisieren; Ausrichten diskotischer Flüssigkristalle; enantioselektive Wagner‐Meerwein‐Umlagerung reiner Aliphaten; photokatalytisch von Furanen zu Pyrrolen; mit Ammoniak zu primären Arylaminen; Metallschrott recyceln mit ionischen Flüssigkeiten; terminale Alkene mit Ni‐Katalysatoren zum (Z)‐ oder (E)‐Alken isomerisieren;neue Fungizide, Medikamente und Alkaloide.

Synthesis of Amidines Via P(III)/P(V)=O Redox Catalyzed In Situ Formation of Imidoyl Chlorides From Amides - Medvaric, Viktorija; Paradies, Jan; Werner, Thomas (Advanced Synthesis and Catalysis)
Amidines are a ubiquitous class of bioactive compounds found in a wide variety of natural products; thus, efficient strategies for their preparation are in great demand. Herein, a novel protocol is reported for the synthesis of amidines based on P III /P V O redox catalysis. This two‐step, one‐pot approach involves the activation of amides via P III /P V O catalyzed in situ formation of imidoyl chloride intermediates which are directly converted upon reaction with amines into the corresponding amidines. Instead of traditionally used toxic and corrosive chloride sources, hexachloroacetone (HCA) is successfully employed as a halide source. The reaction proceeds with low catalyst loading (2 mol%) in BuOAc as the solvent. Under the optimized conditions, 20 amidines are prepared in yields up to 99%. A feasible mechanism is proposed based on experimental results. The synthetic potential of this method is evaluated in the preparation of the tyrosine kinase inhibitor (TKI) Erlotinib.
Keywords: T2; T; CSSD

Straightforward Access to Terpene-Based 1,2-Diols and Their Acetals as Fragrance Ingredients - Stefanow, Vivian; Kell, Lukas; Leduskrasta, Aiga; Eh, Marcus; Panten, Johannes; Werner, Thomas (The Journal of Organic Chemistry)
Keywords: T4; CSSD

Metal-Free Reduction of Nitrous Oxide via PIII/PV═O Cycling: Mechanistic Insights and Catalytic Performance - Zhou, Rundong; Medvaric, Viktorija; Werner, Thomas; Paradies, Jan (Journal of the American Chemical Society)
Keywords: T2; CSSD

Static Light Scattering for Lignin Particle Size Characterization - Makkonen, Janita; Ahvenainen, Patrik; Bertella, Stefania; Kellock, Miriam; Saha, Sanjib; Huber, Klaus; Farooq, Muhammad; Österberg, Monika; Penttilä, Paavo (Particle & Particle Systems Characterization)
Abstract Lignin, a widely available and renewable organic polymer, has several desirable properties and applications. However, as a by‐product of pulp and paper industry, it is mainly burned for energy. Limited understanding of the complex and heterogeneous structure and a shortage of tailored analysis methods hinder its utilization in higher value applications. This study describes and compares the use of two different static light scattering methods, laser diffraction and small‐angle light scattering (SALS), for studying lignin particle size in suspension. The results from laser diffraction showed that the selected particle concentration and absorption coefficient affect the measured sizes especially for particles <1 µm in diameter. For irregularly shaped particles with broad size distributions, sampling is the most important parameter affecting the results. SALS proved an efficient method for obtaining information on particle aggregation by providing primary particle sizes as well as aggregate sizes. Characterization of samples with spherical particles and narrow size distributions is straightforward with both laser diffraction and SALS, whereas the interpretation of results for more heterogeneous samples is less obvious. Static light scattering methods could make lignin particle size analysis more rapid and automated, thus enhancing lignin valorization, but should be applied carefully to avoid systematic errors.

Self-Assembly of Pseudo Isocyanine Chloride in the Presence of Attractive Polyethylene Glycol Crowders - Koch, Leon; Rajput, Satyendra; Richter, Antonio; König, Benedikt; Nayar, Divya; Ebbinghaus, Simon; Huber, Klaus (The Journal of Physical Chemistry B)

Analysis of the Growth Mechanism of Eumelanin Particles by Time-Resolved Static and Dynamic Light Scattering - Kollmann, Fabian; Büngeler, Anne; Splett, Miriam; Strube, Oliver I.; Huber, Klaus (Biomacromolecules)

Coil dimensions of macromolecules in the presence of crowding colloids: Impact of crowder size - Huber, Klaus; Martens, C.M.; Tuinier, R. (Journal of Colloid and Interface Science)

In vacuum metasurface for optical microtrap array - Li, Donghao; Liao, Qiming; Xu, Beining; Zentgraf, Thomas; Narvaez Castaneda, Emmanuel; Zhou, Yaoting; Qin, Keyu; Xu, Zhongxiao; Shen, Heng; Huang, Lingling (Optics Express)
Optical tweezer arrays of laser-cooled and individually controlled particles have revolutionized atomic, molecular, and optical physics. They afford exquisite capabilities for applications in quantum simulation of many-body physics, quantum computation, and sensing. Underlying this development is the technical maturity of generating scalable optical beams, enabled by active components and a high numerical aperture objective. However, such a complex combination of bulk optics outside the vacuum chamber is very sensitive to any vibration and drift. Here, we demonstrate the generation of a 3 × 3 static tweezer array with a single chip-scale multifunctional metasurface element in vacuum, replacing the meter-long free space optics. Fluorescence counts on the camera validate the successful trapping of the atomic ensemble array and showcase a promising strategy for integrated photonics with cold atom systems. The introduction of a polarization independent dual-wavelength metasurface significantly enhances fluorescence collection efficiency while reducing experimental complexity. This approach paves the way for scalable neutral atom platforms and offers a compelling route towards the realization of next generation quantum metasurfaces.

Optisch basierter Digital-Analog-Umsetzer - Kruse, Stephan; Silberhorn, Christine; Brecht, Benjamin; Schwabe, Tobias

Online-Selbstlernkurs zu digitalen Medien im Physikunterricht - Weiler, David Christoph; Burde, Jan-Philipp; Costan, Kasim; Gieshoff, Rike Isabel; Kulgemeyer, Christoph; Lässer, Armin; Plicht, Katja; Riese, Josef; Schubatzky, Thomas (PhyDid B - Didaktik Der Physik - Beiträge Zur DPG-Frühjahrstagung)
Die fortschreitende Digitalisierung bringt große Herausforderungen für die Aus- und Weiterbildung von Lehrkräften mit sich. Während angehende Lehrkräfte bereits von neuen Entwicklungen in der Ausbildung profitieren, sind viele aktive Lehrkräfte bislang nicht ausreichend auf die digitalen Möglichkeiten im Unterricht vorbereitet. Der Kompetenzverbund lernen:digital setzt genau hier an und unterstützt gezielt Lehrkräfte beim Erwerb digitalisierungsbezogener Kompetenzen. Im Rahmen des Verbundprojekts ComeMINT wurde unter anderem ein Online-Selbstlernkurs entwickelt, der sich mit dem Einsatz digitaler Medien im Physikunterricht befasst. Grundlage des Kurses bilden zum einen eine Bedürfnisanalyse unter praktizierenden Physiklehrkräften und zum anderen bereits bestehende Materialien aus der Lehrkräfteausbildung. Der Kurs vermittelt grundlegende Kompetenzen im Umgang mit physikspezifischen digitalen Medien, wie zum Beispiel digitaler Messwerterfassung, Augmented Reality oder Simulationen. In diesem Beitrag werden die Entwicklung und die Inhalte des Selbstlernkurses skizziert, sowie die nachhaltige Aufbereitung der Materialien zur Nachnutzung dargestellt.

Phonon dephasing times determined with time-delayed broadband coherent anti-Stokes Raman scattering - Hempel, F.; Rüsing, Michael; Vernuccio, F.; Spychala, K. J.; Buschbeck, R.; Cerullo, G.; Polli, D.; Eng, L. M. (Physical Review B)
Coherent Raman scattering techniques as coherent anti-Stokes Raman scattering (CARS), offer significant advantages in terms of pixel dwell times and speed as compared to spontaneous Raman scattering for investigations of crystalline materials. However, the spectral information in CARS is often hampered by the presence of a nonresonant contribution to the scattering process that shifts and distorts the Raman peaks. In this work, we apply a method to obtain nonresonant background-free spectra based on time-delayed, broadband CARS (TD-BCARS) using an intrapulse excitation scheme. In particular, this method can measure the phononic dephasing times across the full phonon spectrum at once. We test the methodology on amorphous SiO2 (glass), which is used to characterize the setup-specific and material-independent response times, and then apply TD-BCARS to the analysis of single crystals of diamond and ferroelectrics of potassium titanyl phosphate (KTP) and potassium titanyl arsenate (KTA). For diamond, we determine a dephasing time of 𝜏=7.81 ps for the single 𝑠⁢𝑝3 peak.

Morphological Degradation of Oxygen Evolution Reaction-Electrocatalyzing Nickel Selenides at Industrially Relevant Current Densities - Hiege, Felix; Chang, Chun-Wai; Trost, Oliver; van Halteren, Charlotte E. R.; Hosseini, Pouya; Bendt, Georg; Schulz, Stephan; Feng, Zhenxing; Linnemann, Julia; Tschulik, Kristina (ACS Applied Materials & Interfaces)
We investigated electrodeposited nanoparticulate nickel selenide (pre)catalysts that transform into nickel oxides/oxyhydroxides under oxygen evolution reaction conditions in alkaline solutions. Previous studies of this transformation were conducted at lower current densities than those of industrial relevance (≥1 A cm–2). We used ultramicroelectrodes (UMEs) to achieve such current densities, benefiting from their small size, ensuring low absolute currents and low ohmic drop but high current densities. Morphological degradation of the catalyst material was only observed at current densities exceeding 1 A cm–2 but not for smaller ones. Using X-ray absorption, X-ray photoemission spectroscopy, and X-ray diffraction, we confirmed that the degradation was accompanied by the literature-known transformation of nanoparticulate Ni3Se2 (bulk)/NiSe (surface) into nickel oxyhydroxide. The transformation of the precatalyst goes along with a significant improvement in the charge transfer kinetics observed by decreasing Tafel slopes with ongoing experimental time extracted from cyclic voltammetry (CV) experiments and electrochemical impedance spectroscopy (EIS) in the high-frequency range. However, these kinetic improvements are accompanied by limitations in mass transport concluded from decreasing current responses at high overpotentials in CVs and increasing impedance in the low-frequency range of the EIS spectra after extended CV cycling. These mass transport limitations originated from morphological degradations at the UME exceeding 1 A cm–2 which we proved by applying identical location scanning electron microscopy. This has not been reported in studies that have been limited to lower current densities before. Our findings showcase how UMEs can be used to study (pre)catalysts (herein nickel selenides) under current densities of industrial relevance in the absence of ohmic drop-related ambiguities, combined with in-depth materials characterization studies, e.g., identical location microscopy and advanced spectroscopic methods. This approach enables direct evaluation and comparison of catalyst materials and thus demonstrates how to overcome long-standing limitations of electrocatalyst design and testing.
Keywords: Electrocatalysis; oxygen evolution reaction; nickel selenide; microelectrode

Water-assisted proton conductivity and a magnetic study of heterotrinuclear oxalate-bridged compounds: molecular precursors for the Mn2CrO4 spinel - Lozančić, Ana; Burazer, Sanja; Wagner, Tobias; Molčanov, Krešimir; Pajić, Damir; Androš Dubraja, Lidija; Tiemann, Michael; Jurić, Marijana (Journal of Materials Chemistry C)
Novel oxalate-bridged heterotrinuclear complexes [A][Mn2Cr(bpy)2(H2O)2Cl2(C2O4)3] (A = (CH3)2(C2H5)NH+ (1) and (CH3)(C2H5)2NH+ (2); bpy = 2,2′-bipyridine) were synthesized using an aqueous solution of [A]3[Cr(C2O4)3] as a building block in reaction with Mn2+ ions and with the addition of the N-donor ligand bipyridine. The isostructural heterometallic complex salts were characterized by single-crystal and powder X-ray diffraction, infrared and impedance spectroscopy, thermal analysis and magnetization measurements. The trinuclear anion [{Mn(bpy)(H2O)Cl(μ-C2O4)}2Cr(C2O4)]− consists of two [Mn(bpy)(H2O)Cl]+ units bridged by the [Cr(C2O4)3]3− anion, which acts as a bidentate ligand towards each of the manganese atoms. The anions are hydrogen bonded to each other via coordinated chloride anions, water molecules and oxygen oxalate atoms, resulting in two-dimensional (2D) hydrogen bonding layers. Compounds exhibit water-assisted proton conductivity behaviour, which was investigated at different temperatures and relative humidities (RH). At 25 °C, an increase in RH from 60% to 93% resulted in an obvious proton conducting switch from 9.1 × 10−11 to 5.6 × 10−5 S cm−1 for 1 and from 7.4 × 10−10 to 1.8 × 10−6 S cm−1 for 2, corresponding to high on/off ratios of about 106 for 1 and 104 for 2. In situ powder X-ray diffraction (PXRD) analysis showed that unit cell parameters of compounds 1 and 2 slightly increase when exposed to humid conditions. This confirmed that incorporation of water molecules into structures with pores and voids causes the proton conductivity switching phenomenon. Magnetic susceptibility measurements indicate a ferromagnetic interaction between Cr3+ and Mn2+ ions bridged by the bis(bidentate) oxalate group. The prepared compounds 1 and 2 were explored as single-source precursors for the formation of spinel oxide by their thermal treatment. With increasing temperature, the spinel composition changed according to the formula Mn1+xCr2–xO4 (0 ≤ x ≤ 1), where x = 0.7 at 500 °C and x = 1 at 900 °C when tet[MnII]oct[MnIIICrIII]O4 is formed. The (micro)structure, morphology, and optical properties of spinel Mn2CrO4 were characterized by PXRD, scanning electron microscopy and UV-Vis diffuse reflectance spectroscopy. The photocatalytic activity of this oxide in degradation of the methylene blue dye under Vis irradiation without and with the support of hydrogen peroxide was further investigated.

Fast‐Responding O2 Gas Sensor Based on Luminescent Europium Metal‐Organic Frameworks (MOF‐76) - Zhao, Zhenyu; Weinberger, Christian; Steube, Jakob; Bauer, Matthias; Brehm, Martin; Tiemann, Michael (Advanced Functional Materials)
The increasing demand for advanced sensing technologies drives the development of chemical sensors using innovative materials. In gas sensing, optical sensors are often used to detect gases such as CO, NOx, and O2. Oxygen sensors typically incorporate dyes into oxygen-permeable matrices like polymers, silica, or zeolites. Alternatively, semiconductor surface chemistry can enable O2 detection. However, these approaches are often limited by slow response and recovery times and low selectivity, restricting their practical applications. The metal-organic framework MOF-76(Eu) and its yttrium-modified variant, MOF-76(Eu/Y) are reported to exhibit highly reversible and fast optical responses to varying O2 concentrations. Time-resolved emission measurements are performed over short (seconds) and long (hours) timescales using N2 and synthetic air mixtures. Cross-sensitivity to humidity is analyzed. Multichannel scaling photon-counting experiments confirm quenching at the linker level, as the emission lifetime remains nearly constant. Yttrium significantly improves stability and performance at room temperature. Structural and optical changes induced by yttrium are investigated. Additionally, MIL-78(Eu), another Eu-BTC-based MOF with a different coordination environment, is synthesized. Unlike MOF-76(Eu), MIL-78(Eu) exhibits distinct optical properties but lacks a reversible response to O2. These results highlight the potential of MOF-76-based materials for high-performance O2 sensing.

Ethical dilemmas in coaching: Diversity and inclusion and the role of the coach - Radtke, Sabine
Keywords: Sports Coaching; Diversity; Intersectionality

Innovative teaching with actionbound: Digital pathways in chemistry education - a practical example from ComeNet Chemistry in the ComeMINT Project - Weiser, David; Ditter, Rebecca; Ditter, David; Siepmann, Karin; Grandrath, Rebecca; Fechner, Sabine; Sommer, Katrin; Bohrmann-Linde, Claudia; Rubner, Isabel (International conference New Perspective on Science Education)